Membangun budaya sekolah efektif melalui kepemimpinan visioner - hilal mahmud (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2016)
The study aim at revealing the model the effective school culture through visionary leadership at SMAN 2 Palopo. This is a qualitative – fenomenolgy field research, while data were collected by employing interview, observation, and study documentation, as well as triangulation technique. The results show that he mechanisms conducted in implementing vision are analizing strategic circles, arranging program in strategic planning, and operasional planning. The strategies conducted in developing the culture of effective school includes: developing commitment of effective culture, giving deepest understanding about vision, missions, and objectives of school, establishing distinct course of policy, and emphasizing the importance of creativity and innovation.